An inverted uterine fundus carrying placenta: How does this happen or why is it mistaken? - Chaudhary, Rashmi; Gurung, Geeta; Amatya, Archana; Saki, Kamala; Maharjan, Shreejana (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> A second gravida with normal antenatal period delivered a baby within an hour of admission and also expelled placenta which appeared at vagina. This placenta was adhererent to the fundus of uterus which was inverted but was persistently pulled out as uterine inversion was unrecognized. This case report will be of help to many of us who may mistake such condition. A habit to palpate the fundus of uterus and make sure it is contracted before controlled cord traction will help making the diagnosis in time. Keywords. Controlled cord traction, fundal attachment of placenta, uterine inversion doi:10.3126/njog.v2i2.1459 N. J. Obstet. Gynaecol 2007 Nov-Dec; 2 (2): 69 - 71